Pemodelan Regresi Berganda Pada Pemanfaatan Tanah Liat Dan Batu Karang Sebagai Adsorben Dalam Pengolahan Greywater - Dho Tawa, Bibiana; Kale, Alfius R.; Hadijah Salim, Siti; E. Selan, Odi Th. (Indonesian Journal of Chemical Research, 2018)
The aims of this research are to determine the adsorbent properties, the effect of flow rate and ratio of adsorbent in lowering COD, turbidity, pH levels, and to determine the effect of flow rate interaction and adsorbent ratio in decreasing COD, turbidity and pH levels. This research was conducted with Completed Random Design (CRD) 23 consisting of 2 independent variables namely flow rate (0.2; 0.5; and 0,7 mL/s) and ratio of adsorbent (w/w) of clay : coral (1:1; 1:2; and 2:1) with 3 times replications. The result of the test of the adsorbent properties showed that the clay has hihger acidity and surface area then coral reef, and the coral content of coral reefs is 38.65 %. The flow rate and the ratio of adsorbent based on results of the study also reinforced by the ANOVA test give effect on the levels of COD and turbidity while the interaction of this two variables have an effect on the COD content. The best treatment based on Duncan Multiple Range Test (DMRT) was at 0.7 mL/s flow rate with a 1:1 adsorbent ratio. The multiple regression model for this study is Y =160.3 – 171.17X1 -188.83X2 + 31.67X1X2 + 146.67X12 + 66.67X22.